PENGARUH MEDIA AUDIO VISUAL BERBASIS VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR MATA PELAJARAN PEMELIHARAAN MESIN KENDARAAN RINGAN - Sri Kumalasari; Muhammad Yahya; Syafiuddin Parenrengi; Amiruddin (UNM Journal of Technology and Vocational, 2024)
This research is a quasi-experimental research (as if experimental) by design Control Group Design Pre Test & Post Test which aims to determine the effect of learning video-based audio-visual media on improving student learning outcomes. The population in the research class XI TKR with a total of 56 students consisting of 28 experimental class students and 28 control class. The sample in the study was carried out using the technique (Simple Random Sampling) because the taking of sample members from the population is done randomly. Each student will randomly choose a roll of paper that says the experimental class and the control class. The results of the descriptive statistical analysis research to obtain an overview of the increase in student learning outcomes in the experimental class obtained an average value pre test 46.25 and post test 85.36 while the control group obtained an average value pre test 49.64 and post test 67.50 after being given the highest value treatment results post test the experimental class is higher than the control class. The results of the hypothesis test to obtain the effect of audio-visual media based on video learning based on the calculation of the hypothesis test (independent sample t test) shows a sig (2-tailed) value of 0.000 <0.05 H0 rejected and Ha accepted. The value of t is also obtained tcount of 6,578 and ttable of 2,048. because tcount = 6.578 > ttable= 2.048 points H0 rejected and Ha accepted, which means there is an influence on the use of learning video-based audio-visual media. Index calculation resultsgain to obtain the effectiveness of the use of audio-visual media based on video learning experimental class obtained valuegain of 0.728 in the high category while the control class obtained a valuegain of 0.355 medium category. This shows the effectiveness of using audio-visual media based on video learning to improve student learning outcomes compared to conventional methods.